Desempenho de duas espécies florestais em combinação com casca de arroz na fabricação de painéis cimentomadeira - Lilge, Daniela Silva (2009)
The present paper had as objective the evaluation of performance of panels composed by cement and different proportions of two combined wooden species with rice husk. There, were applied treatments where the levels of wooden residues were 0, 25, 50, 75 and 100%, while the proportion of rice husk was 100, 75, 50, 25 and 0%, respectively. The wood species in the study were Eucalyptus grandis W. Hill ex Maiden and Pinus elliottii Engelm. Physical properties (specific mass, humidity drift, water absorption and swelling thickness at 2 and 24 hours) and mechanical resistance (static flexion; internal connection; and screw with drawell). The panels produced with pine particles presented worse physical characteristics; water absorption and thickness swelling was larger comparing to the panels manufactured with eucalyptus residues. The addition of rice husk, however, improved the physical properties of the manufactured panels with particles of both species. Increasing the amount of rice husks, showed less absorption of water and thickness swelling. The mechanical properties of the panels were affected positively with the addition of larger amounts of wood particles; pine presented better results for internal bond and modulus of elasticity. While presented better results in the property of modulus of rupture. Related to the behavior of the panels in respect to the property of resistance to screw with drawell, the particles of pine generated more resistant boards, with exception of the treatment of 100% of particles of pine that showed inferior values than eucalypt. The addition of rice husks represented loss of mechanical resistance for all the treatments in all the evaluated properties.